Andean Indians in Chilean brotherhoods (Santiago, 17th century) - Valenzuela Márquez, Jaime (2007)
From the conquest expeditions to the individual migratory flow that developed during the 17th century, numerous Andean indigenous people settled in Santiago. Several dictated wills and left traces in ecclesiastical documents that allow us to observe their participation in the religious brotherhoods of the city. These can be seen, in turn, as a preferential channel for sociability and counter-reformist religiosity and, at the same time, as a privileged space for the insertion and social mobility of a diverse population. Indeed, not only Andeans, but also Huarpes, Juríes and Mapuches, as well as mestizos, Africans and Hispano-Creoles of diverse origin and hierarchy, were designing an increasingly multi-ethnic and multicultural urban society, which was also echoed in the formation of brotherhoods. Santiago, which complicated the religious, social and cultural experience that took place inside.